Penerapan Persediaan Economic Order Quantity (EOQ) untuk Meningkatkan Efisiensi Pengendalian Persediaan Bahan Baku Makmur Jaya - Pesta Gultom; Michael Lee Manurung; Ekin Geronimo (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Makmur Jaya is a company engaged in the production of snacks and faces challenges in controlling raw material inventory, such as inaccuracy in the number of orders and high storage costs. This study aims to apply the Economic Order Quantity (EOQ) method to improve efficiency in inventory management. The EOQ method is used to determine the optimal number of orders that can minimize the total cost of inventory, including ordering and storage costs. The results of the analysis show that the implementation of EOQ is able to significantly reduce the total cost of inventory compared to the conventional method that has been used by the company. In addition, EOQ also provides benefits in scheduling raw material orders more efficiently and systematically. Thus, the application of the EOQ method is an effective strategy in improving the efficiency of raw material inventory control in Makmur Jaya.